Learning styles of cocoa farmers in training scenarios in Colombia - Hincapié Echeverri, Oscar Darío (2020)
This analysis arose from a study carried out by the University of Antioquia –(UdeA) and the Corporación colombiana de investigacion agropecuaria – (Agrosavia), which, seeing the need to identify learning styles in the adult population and especially in rural communities, designed a Methodology of identification of learning styles applicable to the agricultural sector – (Mideas). This methodology has a toolbox that provides the facilitator with different alternatives in their transfer processes. To continue this contribution, learning styles were identified with cocoa farmers who attend trainings in Antioquia, Cauca, Caquetá, and Santander in Colombia. In this analysis, a physical survey was used that was completed by 183 cocoa farmers, where it addresses four socio-cognitive dimensions (Motivational, Social, Perceptual and Strategic). The results in the motivational dimension were 61.2% innovative, in the social dimension 66.7% were identified as participatory, in the perceptual dimension it was the most equitable dimension of the four in its variables, since the percentages between auditory (27.9%), visual (21.9%) and reader-writers (20.2%), and in the strategic dimension, the large percentage with 61.2% identified the farmers as practical. It was concluded that, in Antioquia and Santander, traditionally cocoa farmers, they prefer to expand their knowledge, while in Cauca and Caquetá, considered neo-cocoa farmers, they prefer to acquire new knowledge.